2021
DOI: 10.7150/thno.48436
|View full text |Cite
|
Sign up to set email alerts
|

Covalent modification of Keap1 at Cys77 and Cys434 by pubescenoside a suppresses oxidative stress-induced NLRP3 inflammasome activation in myocardial ischemia-reperfusion injury

Abstract: Background and Purpose: Kelch ECH-associating protein 1 (Keap1) is a crucial chaperonin for E3 ubiquitin ligases. Modification of the key reactive cysteine residues in Keap1 affects the interaction between Keap1 and its substrate nuclear factor erythroid 2-related factor 2 (Nrf2), subsequently regulating oxidative stress and NLPR3 inflammasome activation, which are important factors for myocardial ischemia-reperfusion injury (MI/RI). Pubescenoside A (PBA), an active compound from Ilex pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…These PRRs recognize different PAMPs and DAMPs. Among them, NLRP3 is most frequently investigated and has the most diverse activators 3 , 6 , 30 , 40 , 41 . Unlike other PRRs, NLRP3 and pyrin can be activated without a direct contact with their activators.…”
Section: Inflammasome Complex Formation and Activationmentioning
confidence: 99%
“…These PRRs recognize different PAMPs and DAMPs. Among them, NLRP3 is most frequently investigated and has the most diverse activators 3 , 6 , 30 , 40 , 41 . Unlike other PRRs, NLRP3 and pyrin can be activated without a direct contact with their activators.…”
Section: Inflammasome Complex Formation and Activationmentioning
confidence: 99%
“…Nuclear factor erythroid 2-related factor 2 (NRF2), a transcription factor, reportedly protects against various oxidative stress-induced diseases and has been suggested as a promising therapeutic target for cardiac oxidative damage (Tian et al, 2021a). Increasing evidence has shown that NRF2 activity is limited in a normal cellular microenvironment (Cheng et al, 2021). However, under constant oxidative conditions, NRF2 released in the cytoplasm from inactivated NRF2-Kelch-like ECH associated protein 1 (Keap1) complex promotes the expression of gene subsets correlated with antioxidant responses such as genes encoding heme oxygenase-1 (HO-1), oxidoreductase 1 (NQO1), and other antioxidant proteins through binding to the antioxidant response elements (ARE) sequences (Nezu and Suzuki, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Given that IL-32 has been implicated in Crohn's disease (18) and rheumatoid arthritis, both of which are associated with inflammation, the present study hypothesized that this cytokine may play a primary role in the development of MIRI. Human cardiomyocytes were used to establish an in vitro model to mimic MIRI by hypoxia and reoxygenation (H/R) (19). The present study investigated the effects of IL-32 on inflammation, oxidative stress and apoptosis in H/R-induced cells.…”
Section: Introductionmentioning
confidence: 99%
“…Human cardiomyocytes were used to establish an in vitro model to mimic MIRI by hypoxia and reoxygenation (H/R) ( 19 ). The present study investigated the effects of IL-32 on inflammation, oxidative stress and apoptosis in H/R-induced cells.…”
Section: Introductionmentioning
confidence: 99%